The role of the state in promoting microfinance institutions - Lapenu, Cecile (International Food Policy Research Institute, 2000)
In a context of liberalized financial systems, microfinance allows millions of households, usually excluded from classical financial services, to begin or reinforce their own activities and become microentrepreneurs. Yet, in spite of the success of numerous microfinance institutions (MFI), many difficulties remain which must be urgently resolved in view of their ambitious objectives. First, a large number of the rural households still lack access to financial services. Second, most of the existing MFI are not yet financially sustainable. Finally, while funds from governments and donors are rapidly increasing, financial institutions still need solid foundations to avoid management failures. These issues raise questions of the role of the state to promote MFI including (1) which state-owned institutions may be necessary? (2) which level and type of subsidization of the financial institutions can be accepted? (3) what can be the choice for the state between alternative investments in financial institutions or complementary services? (4) what are the necessary conditions for creating a favorable environment? This paper presents the evolution of views on the role of the state in the financial system including theoretical and empirical points of view from the interventionist period of the 1960s and 1970s to the current period of liberalization. Based on country case studies illustrating the divergent role of the state in the development of the rural financial system, the paper reviews the respective role of the state, the NGO and the private commercial banks in increasing their outreach and in adopting microfinance innovations. It also analyzes different issues regarding regulation of MFI.